SUSTAINABILITY BUSINESS by IMPROVING EMPLOYEE’S PRODUCTIVITY: A CASE STUDY ON PT. MORICH INDO FASHION AT KARANGJATI, SEMARANG REGENCY - Nurchayati Nurchayati; Sukardi Sukardi; Heru Eko Prasetyo; Widi Kurniawan (International Journal of Economics and Management Research, 2022)
The purpose of this study was to notice and analyze the increase of employee productivity by the approach occupational health and working environment safety in supporting Business Sustainability PT. Morich Indo Fashion. The research method used was quantitative. The population in this study were all employees of PT. Morich Indo Fashion Karangjati Semarang Regency Quality Control section. The sample used was 72 using the proportional random sampling which was carried out randomly without regard to the existing strata in the population. The analysis used in this study was multiple linear regression analysis. The findings of this study as follows the influence of the role of occupational health and safety and work environment significantly on work productivity. This meant that the role of occupational health and safety and the work environment was positive and significant to the work productivity of PT. Morich Indo Fashion. In sum, the sustainability of the company’s business became more guaranteed.